Respuesta :
[tex]f(x)[/tex] will have a horizontal asymptote of [tex]y=2[/tex] if
[tex]\displaystyle\lim_{x\to\pm\infty}(f(x)-2)=0[/tex]
where at least one of these limits needs to be satisfied. Since we would like
[tex]\dfrac{2x^m}{x+a}-2=\dfrac{2x^m-2(x+a)}{x+a}[/tex]
to converge to 0, we need the [tex]x^m[/tex] term to disappear in the numerator. The only way for that to happen is if [tex]m=1[/tex]. Then
[tex]\dfrac{2x-2(x+a)}{x+a}=-\dfrac{2a}{x+a}[/tex]
and this does indeed approach 0 as [tex]x[/tex] gets arbitrarily large.
Now, in order to have a vertical asymptote at [tex]x=1[/tex], all we need to do is set [tex]a=-1[/tex]. Then
[tex]\displaystyle\lim_{x\to-1}\frac{2x}{x+1}[/tex]
does not exist, as required.
[tex]\displaystyle\lim_{x\to\pm\infty}(f(x)-2)=0[/tex]
where at least one of these limits needs to be satisfied. Since we would like
[tex]\dfrac{2x^m}{x+a}-2=\dfrac{2x^m-2(x+a)}{x+a}[/tex]
to converge to 0, we need the [tex]x^m[/tex] term to disappear in the numerator. The only way for that to happen is if [tex]m=1[/tex]. Then
[tex]\dfrac{2x-2(x+a)}{x+a}=-\dfrac{2a}{x+a}[/tex]
and this does indeed approach 0 as [tex]x[/tex] gets arbitrarily large.
Now, in order to have a vertical asymptote at [tex]x=1[/tex], all we need to do is set [tex]a=-1[/tex]. Then
[tex]\displaystyle\lim_{x\to-1}\frac{2x}{x+1}[/tex]
does not exist, as required.